Community‐based naloxone coverage equity for the prevention of opioid overdose fatalities in racial/ethnic minority communities in Massachusetts and Rhode Island. (5th December 2021) - Nolen, Shayla; Zang, Xiao; Chatterjee, Avik; Behrends, Czarina N.; Green, Traci C.; Kumar, Aranshi; Linas, Benjamin P.; Morgan, Jake R.; Murphy, Sean M.; Walley, Alexander Y.; Yan, Shapei; Schackman, Bruce R.; et al.
Abstract: Background and aims: Opioid‐related overdose death rates continue to rise in the United States, especially in racial/ethnic minority communities. Our objective was to determine if US municipalities with high percentages of non‐white residents have equitable access to the overdose antidote naloxone distributed by community‐based organizations. Methods: We used community‐based naloxone data from the Massachusetts Department of Public Health and the Rhode Island non‐pharmacy naloxone distribution program for 2016–18. We obtained publicly available opioid‐related overdose death data from Massachusetts and the Office of the State Medical Examiners in Rhode Island. We defined the naloxone coverage ratio as the number of community‐based naloxone kits received by a resident in a municipality divided by the number of opioid‐related overdose deaths among residents, updated annually. We used a Poisson regression with generalized estimating equations to analyze the relationship between the municipal racial/ethnic composition and naloxone coverage ratio. To account for the potential non‐linear relationship between naloxone coverage ratio and race/ethnicity we created B‐splines for the percentage of non‐white residents; and for a secondary analysis examining the percentage of African American/black and Hispanic residents. The models were adjusted for the percentage of residents in poverty, urbanicity, state and population size. Results: Between 2016 and 2018, the annual naloxone coverage ratios range was 0–135. There was no difference in naloxone coverage ratios among municipalities with varying percentages of non‐white residents in our multivariable analysis. In the secondary analysis, municipalities with higher percentages of African American/black residents had higher naloxone coverage ratios, independent of other factors. Naloxone coverage did not differ by percentage of Hispanic residents. Conclusions: There appear to be no municipal‐level racial/ethnic inequities in naloxone distribution in Rhode Island and Massachusetts, USA.